The use of ICTs as an empowering tool in the teaching-learning process of Arabic as a foreign language - El Khaymy, Asmaa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The emergence of new forms of information and communication technologies (ICTs) in the socio-cultural arena has generated considerable changes in several aspects of our daily life. Therefore, in order to optimize the teaching process and keep up with the necessities of a rapidly changing environment, more and more educational institutions ended up raising up the challenge of integrating the use of new technologies in their day-to-day activities. The present article places emphasis on the importance of integrating ICTs in the process of teaching and learning spanish as a foreign language, illustrating the added value of taking advantage of some technological tools and resources inside and outside the classroom setting. To this end, it carries out a descriptive and explanatory analysis of these tools in the hope that students could take advantage thereof.